2016
DOI: 10.1007/s13277-016-5267-8
|View full text |Cite
|
Sign up to set email alerts
|

Myopodin methylation is a prognostic biomarker and predicts antiangiogenic response in advanced kidney cancer

Abstract: Myopodin is a cytoskeleton protein that shuttles to the nucleus depending on the cellular differentiation and stress. It has shown tumor suppressor functions. Myopodin methylation status was useful for staging bladder and colon tumors and predicting clinical outcome. To our knowledge, myopodin has not been tested in kidney cancer to date. The purpose of this study was to evaluate whether myopodin methylation status could be clinically useful in renal cancer (1) as a prognostic biomarker and 2) as a predictive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Synaptopodin-2 (SYNPO2), also known as myopodin, is actin-bundling protein, and is characterized as a putative tumour suppressor in aggressive cancers [34][35][36][37][38]. Frequent loss of expression and genetic alteration of SYNPO2 have been found, in various advanced cancers, to be correlated with high rates of clinical relapse and metastasis [35,[37][38][39][40][41]. Further studies revealed that suppression of SYNPO2 expression promoted tumour growth, migration, and invasion, thus promoting tumour metastasis [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…Synaptopodin-2 (SYNPO2), also known as myopodin, is actin-bundling protein, and is characterized as a putative tumour suppressor in aggressive cancers [34][35][36][37][38]. Frequent loss of expression and genetic alteration of SYNPO2 have been found, in various advanced cancers, to be correlated with high rates of clinical relapse and metastasis [35,[37][38][39][40][41]. Further studies revealed that suppression of SYNPO2 expression promoted tumour growth, migration, and invasion, thus promoting tumour metastasis [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have focused, so far, on non-coding RNAs as predictive biomarkers of TKIs. Excluding non-coding RNA biomarkers, differential levels of cytokines, some genetic variants, several blood-based molecules, circulating cancer cells and epigenetic patterns have been associated with response to various TKIs (9)(10)(11)(12)(13)(14)(15). It has been shown that the response to sunitinib in mRCC is associated with standard blood serum markers such as C-reactive protein (16) and proangiogenic and proinflammatory cytokine C-X-C motif chemokine ligand containing glutamic acid, leucine arginine motif (17,18).…”
mentioning
confidence: 99%
“…128 Some studies have shown the prognostic role of DNA methylation in TKI treatment. 130,131 Tumor microenvironment factors…”
Section: Dna Methylationmentioning
confidence: 99%
“…Overexpression of QPCT promoted sunitinib resistance through Ras/Raf/ERK signaling pathway 128 . Some studies have shown the prognostic role of DNA methylation in TKI treatment 130,131 …”
Section: Molecular Pathways Associated With Resistance To Treatment W...mentioning
confidence: 99%